Pathology and molecular detection of fowlpox virus in chickens in Nigeria (African Journal of Biomedical Research, 2021)
Fowlpox is a relatively slow developing disease characterized by discrete, proliferative lesions on the skin of toes, legs or head, and/ or mucous membranes of the mouth and upper respiratory tract of birds. Several diseases of birds such as infectious coryza, infectious laryngotracheitis, Mareks, and vitamin A deficiency can be confused with fowlpox, therefore there is need for an accurate and reliable method of diagnosis. A combination of histopathology, Polymerase Chain Reaction (PCR) and sequence analysis can be used to arrive at the confirmatory diagnosis of the disease. Consequently, fifty scab samples from suspected cases of fowlpox from backyard poultry in Ibadan, Nigeria were collected, and PCR, sequencing with sequence analysis were employed to detect and characterize the open reading frame 168 (39 kDa core protein) gene of the virus. Also, lesions from the eyelids were excised and histopathology was carried out. Thirty-one out of 50 samples (62%) tested positive for fowlpox based on PCR and sequence analysis. Histopathology revealed the presence of dermal hyperplasia and Bollinger bodies which are confirmatory of fowlpox. PCR amplification, sequence analysis of 39 kDa core protein gene and histopathology provide a reliable diagnosis of fowlpox.